Twice : a novel [compact disc, unabridged] - Albom, Mitch, 1958- (Good morning America book club., 2025)
When he is eight years old, Alfie Logan discovers the magical ability to get a second chance at everything. The one catch: he must accept the consequences of his second try, for better or worse. He grows up correcting mistakes and even taking dangerous near-death risks. Years later, as he is interrogated by a detective for cheating at a casino, Alfie's full story comes to light.